2003
DOI: 10.2337/diacare.26.7.2209
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 98 Children and Adolescents Diagnosed With Type 2 Diabetes by Their Health Care Provider at Initial Presentation

Abstract: A lthough the number of children and youth with type 2 diabetes is increasing, a clear case definition that describes children with type 2 diabetes at presentation remains elusive. Most initial diagnoses are decided on the clinical picture at presentation (1). Characteristics and risk factors have been outlined in several review and clinical articles (2-4). The purpose of this study was to describe the characteristics of youth presenting for an initial visit to the outpatient clinic of a large tertiary childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 3 publications
0
58
1
1
Order By: Relevance
“…With few exceptions, these trials, especially those with high statistical power and thiazide-based regimens, showed benefit for CVD outcomes. [3][4][5][6][7][8] This evidence, which provided a basis for recommending thiazides or ␤-blockers as first-step drugs in most editions of US guidelines through 1997, 9 needs to continue to be given due weight in practice and practice guidelines.…”
Section: Trials Of Blood Pressure Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…With few exceptions, these trials, especially those with high statistical power and thiazide-based regimens, showed benefit for CVD outcomes. [3][4][5][6][7][8] This evidence, which provided a basis for recommending thiazides or ␤-blockers as first-step drugs in most editions of US guidelines through 1997, 9 needs to continue to be given due weight in practice and practice guidelines.…”
Section: Trials Of Blood Pressure Reductionmentioning
confidence: 99%
“…This remained the situation through the 1990s, despite publication of results from the BMRC trial of treatment of hypertension in older adults, the ␤-blocker arm of which showed no significant reduction in either stroke or CHD events compared with placebo. 7 In keeping with practice trends, a cardioselective ␤-blocker, atenolol, was selected in this trial; in this arm, systolic BP was less well controlled for the first year than in the hydrochlorothiazide arm.…”
Section: The Evidence For and Against ␤-Blockersmentioning
confidence: 99%
See 3 more Smart Citations